O ensino de matemática nos anos iniciais em tempos de cibercultura : refletindo acerca da formação do pedagogo - Souza, Caroline Tavares de (2017)
Mathematics learning is a challenge in students’ academic lives, although its importance in society has never been so significant and necessary as from the advancement of digital technologies. It is believed that problems related to the learning of mathematics have their origin in the early years of elementary school, where students are expected to learn the basis of mathematical knowledge. However, evidence found in this study points out that the teacher who is in the classroom at this stage, in most cases, does not have the necessary training related to the concepts and mathematical contents necessary to teach mathematics in a contextualized and creative way. The insufficient training related to Mathematics in the undergraduate courses in Pedagogy causes to teachers who already work or will work in schools, in the early years, gaps that are not healed in their initial training. It is assumed that students of Pedagogy know such contents and that they have been acquired in their formation in elementary school, prior to their admission in the undergraduate course, a fact that does not seem to be confirmed. This idiosyncrasy ends up passing on responsibility for this training to the student of Pedagogy and not to the undergraduate course. This qualitative-exploratory research, supported by a case study involving invited teachers from public and private schools in the Porto Alegre and professors of Pedagogy undergraduate courses, aimed to investigate the formation of pedagogues, regarding the teaching of Mathematics in the early years of elementary school, trying to identify possible gaps and alternatives of continuing education, especially those who have access to the use of open digital spaces / resources. Some of the theoretical references used are: Tardif, Nóvoa, Lévy, Prensky, Lorenzato and Nacarato. As a result of this research, it is highlighted the approach given in the undergraduate courses in Pedagogy focused on the methodological aspects of mathematics teaching, not contemplating the specific training of the mathematical contents that will be taught by these teachers. The study also emphasized that open digital spaces / resources are not being discussed and / or used in teachers’ training in the early years of elementary school, so it is difficult to use these spaces and resources in both continuing education and teaching practice. Something significant that was found in the research was that there are mathematics laboratories in some private schools, which rely on materials and specialists to support mathematics teaching as well as teacher training. Another interesting data found in the research was the continuing education in service, especially in private schools, something that helps in the reconstruction and re-signification of teacher's relationship with Mathematics, allowing him/her to teach a different way of how he/she learned. It is expected that this study has provided elements for a reflection on the need to revise the curricula of Pedagogy courses in a broader perspective than just the inclusion of one or more subjects dealing with mathematical contents. Also, it is expected that this research points out alternatives for teachers or future teachers on how to look for complementary training using the open digital spaces / resources available online.